2017
DOI: 10.1016/j.jsb.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural, material and crystallographic description of endophytic masses – A possible damage response in shark and ray tessellated calcified cartilage

Abstract: The cartilaginous endoskeletons of elasmobranchs (sharks and rays) are reinforced superficially by minute, mineralized tiles, called tesserae. Unlike the bony skeletons of other vertebrates, elasmobranch skeletons have limited healing capability and their tissues' mechanisms for avoiding damage or managing it when it does occur are largely unknown. Here we describe an aberrant type of mineralized elasmobranch skeletal tissue called endophytic masses (EPMs), which grow into the uncalcified cartilage of the skel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 74 publications
(100 reference statements)
2
33
0
Order By: Relevance
“…Recently, Seidel et al (2017) reported aberrant, mineralized structures in cartilage of elasmobranchs, which they referred to as endophytic masses (EPMs) and which phenotypically shows several resemblances with the EMS of this study. These EPMs are closely associated with tesserae but reveal distinct characteristics, such as hypermineralized dead cells, a "brushstroke-like" pattern of randomly oriented mineralized bundles in the matrix, crystal strings in the mineral phase and a frayed interface with the surrounding unmineralized cartilage (Seidel et al, 2017).…”
Section: Comparison With Pathological Mineralized Structuresmentioning
confidence: 58%
See 2 more Smart Citations
“…Recently, Seidel et al (2017) reported aberrant, mineralized structures in cartilage of elasmobranchs, which they referred to as endophytic masses (EPMs) and which phenotypically shows several resemblances with the EMS of this study. These EPMs are closely associated with tesserae but reveal distinct characteristics, such as hypermineralized dead cells, a "brushstroke-like" pattern of randomly oriented mineralized bundles in the matrix, crystal strings in the mineral phase and a frayed interface with the surrounding unmineralized cartilage (Seidel et al, 2017).…”
Section: Comparison With Pathological Mineralized Structuresmentioning
confidence: 58%
“…In order to assess the characteristics and origin of this structure, a comparison with other abnormal tissues that share similar traits with this EMS is provided. Although some similarities hinted towards a neoplasm derived from hyaline cartilage, the phenotype corresponds most to a similar structure found in the cartilaginous endoskeleton of elasmobranchs (Seidel et al, ).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Cells within the neural arch, basidorsal and basiventral cartilages can be categorised with respect to morphology, and distribution within the cartilage. Chondrocytes located deeper in the cartilage interior ( Figures 2A, 3B hypertrophy, which has not been observed in chondrichthyans (Dean et al, 2015;Seidel et al, 2017b; but see Debiais-Thibaud [2019] for a summary of contrary opinions).…”
Section: Cellular Aspectsmentioning
confidence: 97%
“…The functions of diseased and broken calcified tissues, such as bone and teeth, can be restored by applying orthopedic and dental implants. The good fixation of these implants in the body depends on the presence of a stable and powerful interface between the bone and the implant . Bio inert metallic implants are used as high load bearing bones because of their superior strength, biocompatibility, and corrosion resistance .…”
Section: Introductionmentioning
confidence: 99%